PERSEPSI MASYARAKAT TERHADAP DAMPAK EKONOMI BALKONDES DI DESA BOROBUDUR DAN TUKSONGO, MAGELANG - Octaviani Gita Putri; Moch Bagoes Pakarti (Bogor Hospitality Journal, 2023)
Community-based tourism development is very important because the community is the main component in supporting the development of the regional tourism economy. One example of such a program is the Village Economic Center (Balai Ekonomi Desa/ Balkondes). This program is a program from the Ministry of BUMN (State- owned enterprises) to help improve the economic welfare of rural communities. Therefore, this study aims to determine how the community's perceptions of the economic impact of Balkondes in Borobudur and Tuksongo Villages, Magelang because community's perceptions and attitudes are related to the support given for the success of further tourism development. The primary data were taken from observations and in-depth interviews. The secondary data is taken from article data, Balkondes data, theory and others. Based on the research results, if it is related to positive perceptions, the similarities are increased income, employment and PADes (Village original income); while the difference is that the Tuksongo community feels an increase in village development, and the Borobudur community feels that the impact of development is not that significant. If it is related to negative perceptions, the similarity is that the economic impact of Balkondes has not been maximized due to challenges from incompetent human resources; while the difference is community of Borobudur who feel that the presence of Balkondes can increase competition even unfairly